Past, present, and future: Critical analysis of use of gastric bands in obese patients - Snyder B (Dove Medical Press, 2010)
Brad Snyder, Todd Wilson, Sheilendra Mehta, Kulvinder Bajwa, Emily Robinson, Todd Worley, Kanayochukwu Aluka, Carol Wolin-Riklin, Erik WilsonDepartment of Surgery, University of Texas Health Sciences Center at Houston, TX, USAAbstract: Adjustable gastric banding (AGB) is quickly becoming the most popular bariatric operation performed in the United States and Canada. Patients are particularly fond of the simplicity of the tool, the relatively low morbidity of the surgery, the quick recovery, and overall results. The gastric band has evolved over its 35-year history into a very successful adjustable tool used to restrict food consumption and limit caloric intake. The percent of excessive weight loss after banding can range from 30%–60% and depends on the time out from surgery. Along with weight loss, there is good resolution of the co-morbid conditions that are associated with excess weight and improvements in quality of life demonstrated after banding. Nutrition and follow up are extremely important after banding to ensure good compliance and adequate weight loss. Failure to follow the postoperative diet, exercise regiment, or mechanical failure of the band can lead to failure to lose adequate weight. While there are particular early and late complications associated with this surgery, the safety profile of the AGB is very appealing when compared to other bariatric operations. As we continue to reduce the morbidity of the procedure, the simple adjustable band concept has a lot of potential to remain a primary technique of maintaining long term weight loss. In conclusion, AGB has and continues to play an important role in the treatment of morbid obesity. It offers reasonably good weight loss results with very little morbidity, and the future of the adjustable band is bright.Keywords: adjustable band, gastric, bariatric, operation, surgery, weight loss, lap-band